Ventriculoperitoneal Shunt Drainage Increases With Gravity and Cerebrospinal Fluid Pressure Pulsations: Benchtop Model. Issue 6 (15th September 2021) - Koueik, Joyce; Iskandar, Bermans J; Yang, Zhe; Kraemer, Mark R; Armstrong, Stephanie; Wakim, Victor; Broman, Aimee Teo; Medow, Joshua; Luzzio, Christopher; Hsu, David A
Abstract: BACKGROUND: There have been few improvements in cerebrospinal fluid (CSF) shunt technology since John Holter introduced the silicon valve, with overdrainage remaining a major source of complications. OBJECTIVE: To better understand why valves are afflicted by supra-normal CSF flow rates. We present in Vitro benchtop analyses of flow through a differential pressure valve under simulated physiological conditions. METHODS: The pseudo-ventricle benchtop valve testing platform that comprises a rigid pseudo-ventricle, compliance chamber, pulsation generator, and pressure sensors was used to measure flow rates through a differential pressure shunt valve under the following simulated physiological conditions: orientation (horizontal/vertical), compliance (low/medium/high), and pulsation generator force (low/medium/high). RESULTS: Our data show that pulse pressures are faithfully transmitted from the ventricle to the valve, that lower compliance and higher pulse generator forces lead to higher pulse pressures in the pseudo-ventricle, and that both gravity and higher pulse pressure lead to higher flow rates. The presence of a valve mitigates but does not eliminate these higher flow rates. CONCLUSION: Shunt valves are prone to gravity-dependent overdrainage, which has motivated the development of gravitational valves and antisiphon devices. This study shows that overdrainage is not limited to the vertical position but that pulse pressures that simulate rhythmic (eg, cardiac) and provoked (eg, Valsalva) physiological CSF pulsations increase outflow in both the horizontal and vertical positions and are dependent on compliance. A deeper understanding of the physiological parameters that affect intracranial pressure and flow through shunt systems is prerequisite to the development of novel valves.